2007
DOI: 10.1093/rpd/ncm234
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of radiation doses to patients and surgeons from various fluoroscopically guided orthopaedic surgeries

Abstract: In this study, a mathematical method was used to estimate the entrance surface dose (ESD) to the patient and the scattered dose (Ds) to the operating surgeon during various fluoroscopically guided surgical orthopaedic procedures. For 204 patients, the procedure type, the fluoroscopy time and the highest tube potential and current values observed during fluoroscopy were recorded. For the most often performed procedures (intramedullary nailing of peritrochanteric fractures, open reduction and internal fixation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 11 publications
4
57
2
Order By: Relevance
“…While the use of fluoroscopy during the surgery did not prolong the case, setup and take down of the C-arm, and how that figures into total time in the operating room and potential costs associated with its use were not analyzed. The radiation exposure to the patient and surgeon was not recorded during this study, but these data were reported for numerous orthopaedic procedures that use fluoroscopy [20]. We did not analyze the outcomes for the senior authors individually.…”
Section: Discussionmentioning
confidence: 99%
“…While the use of fluoroscopy during the surgery did not prolong the case, setup and take down of the C-arm, and how that figures into total time in the operating room and potential costs associated with its use were not analyzed. The radiation exposure to the patient and surgeon was not recorded during this study, but these data were reported for numerous orthopaedic procedures that use fluoroscopy [20]. We did not analyze the outcomes for the senior authors individually.…”
Section: Discussionmentioning
confidence: 99%
“…In the next step, only studies where effective radiation to the surgeon was directly measured in the operating theatre were further considered for this review. Studies using indirect measurements or formulas to back calculate surgeon exposure [14][15][16][17][18][19][20][21][22][23][24] as well as studies measuring radiation exposure in Gray only were not further reviewed because of the problem of comparability [25][26][27][28][29][30][31].…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5] Despite this increase in use and the subsequent increase in radiation exposure to the operative team and patient, the long-term effects of exposure to low-dose ionizing radiation remain largely unknown. 4,[6][7][8] There exists strong evidence for an increase in cancer risk for chronic doses greater than 100 mSv and reasonable evidence for an increase in cancer risk at chronic doses above 50 mSv.…”
Section: Introductionmentioning
confidence: 99%